Hubungan Prematur dengan Kejadian Asfiksia Neonatorum di Klinik Fatiha - Yundi, Yundi; Harahap, Dewi Anggriani; Afiah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
In Indonesia, the incidence of neonatal asphyxia in referral hospitals of death due to neonatal asphyxia is 41.94%, the cause of neonatal death is estimated to be intrapartum asphyxia at 21%, while asphyxia in infants is 45% the cause of infant death. Asphyxia is a condition in which newborn babies experience failure to breathe spontaneously and regularly immediately after birth. The impacts of asphyxia include brain damage, hypoxic ischemic encephalopathy, acute kidney failure, respiratory distress, heart failure, entericolitis, necrotizing. Apart from causing infant death, the long-term impacts experienced by children can result in neurological disorders from mental retardation, systemic disorders. central nervous system, heart, kidneys, gastrointestinal tract, liver, blood and lungs. The impact on the mother is psychological disorders such as stress, anxiety and depression due to worries about her baby. The aim of this research is to determine the relationship between prematurity and the incidence of neonatal asphyxia at the Fatiha Clinic in 2022. This research design uses quantitative research methods with a case control approach. Case samples were taken using total sampling technique and control samples used systematic random sampling. The research was carried out at the Fatiha Clinic. The case population in this study was 33 newborns who experienced neonatal asphyxia, while the control population was 141 newborns who did not experience neonatal asphyxia. The research uses a secondary data checklist sheet. Univariate and Bivariate data analysis using the Chi-Squere test. These results show that there is a relationship between prematurity and the incidence of neonatal asphyxia, with a p value of 0.001 < 0.05. For this reason, the clinic can minimize the incidence of baby asphyxia and can improve health services even better by providing counseling to pregnant women to prevent asphyxia in newborn babies.